The Impact Of Service Quality, Price, and Promotion On Customer Satisfaction At Ci’Muna Laundry - Nursiti, Nursiti; Azahra, Rachima (STIE Tri Bhakti, 2025)
This study aims to empirically test the influence of service quality, price, and promotion on customer satisfaction at Ci'Muna Laundry. The population of this study was all customers who have used Ci'Muna Laundry services, and the sample size was 100 respondents. Data collection was conducted by distributing questionnaires to Ci'Muna Laundry customers. The data source used was primary data. This study used Structural Equation Modeling (SEM) Smart PLS 4.1 to determine the relationship between variables X and Y. The conclusion of this study is that service quality has a positive effect on customer satisfaction, price has a negative effect on customer satisfaction, and promotion has a negative effect on customer satisfaction. The Adjusted R-Square (Adjusted R²) indicates that 71% is influenced by service quality, price, and promotion, while the remaining 29% is influenced by other variables outside this study.